Long-term Persistence of Innate Lymphoid Cells in the Gut After Intestinal Transplantation. Issue 10 (October 2017) - Weiner, Joshua; Zuber, Julien; Shonts, Brittany; Yang, Suxiao; Fu, Jianing; Martinez, Mercedes; Farber, Donna L.; Kato, Tomoaki; Sykes, Megan
Abstract : Background: Little is known about innate lymphoid cell (ILC) populations in the human gut, and the turnover of these cells and their subsets after transplantation has not been described. Methods: Intestinal samples were taken from 4 isolated intestine and 3 multivisceral transplant recipients at the time of any operative resection, such as stoma closure or revision. ILCs were isolated and analyzed by flow cytometry. The target population was defined as being negative for lineage markers and double-positive for CD45/CD127. Cells were further stained to define ILC subsets and a donor-specific or recipient-specific HLA marker to analyze chimerism. Results: Donor-derived ILCs were found to persist greater than 8 years after transplantation. Additionally, the percentage of cells thought to be lymphoid tissue inducer cells among donor ILCs was far higher than that among recipient ILCs. Conclusions: Our findings demonstrate that donor-derived ILCs persist long-term after transplantation and support the notion that human lymphoid tissue inducer cells may form in the fetus and persist throughout life, as hypothesized in rodents. Correlation between chimerism and rejection, graft failure, and patient survival requires further study. Abstract : Intestinal biopsy samples from 4 patients with intestinal transplants and 3 patients with multivisceral transplants shows that that donor-derived innate lymphoid cells can persist in transplanted gut for many years (>8) and in some cases longer than donor T cells. Supplemental digital content is available in the text.